Directorate General Of Islamic Community Guidance Practice Regulation Number: Dj.Ii/542 Year 2013 In Increasing The Family Resilience Of West Palu Society Through Marriage Guidelines - Muh. Arief, Haerolah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
Problems in the household ark will eventually stymie the noble ideals of marriage. In this regard, this study is concerned to increase family resilience in the West Palu sub-district through self-collective marriage guidance based on the Directorate General of Islamic Community Guidance Regulation Number DJ. II/542 of 2013. In order to obtain a comprehensive study of the research problem, this study employs a combination of qualitative and quantitative methods. According to the study's findings, the implementation of premarital guidance for prospective brides at the KUA in West Palu District provided benefits but was ineffective. Thus, solution efforts must be made by referring to and following the guidelines for implementing premarital guidance, both in terms of material content and implementation patterns, as well as the existence of institutional support for the Indonesian Ministry of Religion as a budget provider and other institutions, and including premarital guidance as a mandatory requirement in marriage registration requirements.Keywords: Regulation; Family Resilience, Marriage Guidance